PERSEPSI MAHASISWA PADA INFORMASI AKUN INSTAGRAM LAMBE TURAH - Sari, Eka Yunita (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to determine student perceptions of LAMBE TURAH's Instagram account information in providing information presented by LAMBE TURAH regarding the lives of celebrities. The research method used in this study is quantitative based on a survey method conducted at the Department of Communication Studies, Tadulako University. The sampling technique of this study is random sampling technique, totaling 52 respondents. The data was collected using a questionnaire with Likert measurement scale. The results showed perceptions related to the information provided by the Lambe Turah Instagram account using the theory of the nature of perception. There are 5 indicators consisting of perception based on experience with an average of 66.28%, selective perception 63.59%, presumptive perception 65.77%, evaluative perception 58.46%, contextual perception 63.72%. Students' perceptions of Lambe Turah's Instagram account information help them in getting information presented by Lambe Turah's Instagram account because the information presented is easy to understand and interesting to read. Also, the lambe turah instagram account is entertaining, refreshing and pleasing to the audience by presenting light and relaxed information according to needs.